THE URGENCY OF DIVINE PRINCIPLES IN THE IMPLENTATION OF ARBITRATION AWARD EXECUTION IN INDONESIA - huzaimah al anshori; Sapto Hadi Pamungkas; Aklis Mukhidin; M. Syamsudin (Faculty of Law, Universitas Pekalongan, 2023)
Divine Principles Application in Resolving Business Disputes at the Indonesian National Arbitration Board (BANI) Surabaya. It is important to note that some parties involved in arbitration disputes do not comply with arbitration decisions in Indonesia. Consequently, they resort to measures such as filing annulment requests in the District Court and escalating the matter to the Commercial Court. This situation highlights the urgent need for applying divine principles in executing arbitration awards in Indonesia. The question arises: how do divine principles function in executing national arbitration awards in Indonesia. The author undertakes empirical research utilizing socio-legal approaches, case study approaches, conceptual approaches, and philosophical approaches. To provide solutions for the execution of arbitration awards in Indonesia, various theories are employed, including Grundnorm theory, the theory of legal consciousness and compliance, natural law theory, and the theory of pacta sunt servanda. The principle of divinity, as reflected in the preamble of decisions stating